Adapting and Validating Digcompedu for Early Childhood Education Students Through Expert Competence Coefficient - Silva-Quiroz, J (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Digital teaching competence (DTC) is key for the teaching profession at any educational level. In early childhood education, DTC poses an important challenge due to the particularities of integrating digital technologies into work with infants. This article proposes an adaptation of DigCompEdu for early childhood education. The construction of this proposal was based on international collaboration, an in-depth literature review, and the expert mediation of the authors, resulting in the adaptation of DigCompEdu’s 22 competency descriptors to the field of initial teacher training in early childhood education. Expert competence coefficient K was applied to select 22 experts for the validation process to establish its pertinence, importance, and clarity, who positively evaluated the 22 descriptors of the proposal. The results consist of a DTC proposal in accordance with the DigCompEdu framework for early childhood education students validated by experts, as a starting point for future research for assessing or self-assessment of DTC, and as a guide to define strategies in initial teacher training. © 2025 by the authors.